Studying advanced mathematics in England: findings from a survey of student choices and attitudes - Noyes, Andrew; Adkins, Michael (Taylor and Francis Group, 2016)
The UK Government has set a goal that the ‘vast majority’ of students in England will be studying mathematics to 18 by the end of the decade. The policy levers for achieving this goal include new Core Maths qualifications, designed for over 200,000 students who have achieved good grades at the age of 16 but then opt out of advanced or A-level mathematics. This paper reports findings from a cluster-sampled survey of over ten thousand 17-year-olds in England in 2015. Participants’ views on post-16 mathematics are presented and discussed. The main finding is that they are strongly opposed to the idea of compulsory mathematical study, but are less antithetical to being encouraged to study mathematics beyond 16. We consider how attitudes vary by gender, prior attainment, study patterns and future aspirations. The paper considers the implications of these findings in the current policy landscape.